The Role of Training and Development in Enhancing Employee Engagement: A Systematic Literature Review - Tukiran, Martinus; Lisa Chandrasari Desianti (Universitas Pelita Harapan, 2025)
Employee engagement has emerged as a critical determinant of organizational performance, yet its relationship with training and development remains fragmented across literature. This study conducts a Systematic Literature Review (SLR) guided by the PRISMA framework to synthesize evidence from the past decade (2015–2025). A structured search of the Scopus database yielded 137 documents, which were narrowed to 88 after applying filters and further screened to a final sample of 10 highly relevant peer-reviewed articles. The findings confirm that training and development initiatives directly foster engagement by signaling organizational support and enhancing employee competencies. Engagement often acts as a mediating mechanism linking training to outcomes such as performance, commitment, and retention, while factors such as leadership quality, digital transformation, and cultural context moderate these effects. The synthesis also underscores that the training–engagement nexus is strongest when development initiatives align with national priorities and socio-cultural expectations. This review contributes to the HRD literature by consolidating fragmented evidence and integrating theoretical perspectives, including social exchange theory, the Job Demands-Resources model, and institutional theory. Practical implications suggest that organizations must treat training as a strategic lever, embedding digital tools and contextual sensitivity to cultivate sustainable employee engagement.